A Novel MAO-B/SSAO Inhibitor Improves Multiple Aspects of Dystrophic Phenotype in mdx Mice - Francesca Gasparella; Leonardo Nogara; Elena Germinario; Lucia Tibaudo; Stefano Ciciliot; Giorgia Piccoli; Francisca Carolina Venegas; Francesca Fontana; Gabriele Sales; Daniele Sabbatini; Jonathan Foot; Wolfgang Jarolimek; et al. (MDPI AG, 2024)
Duchenne muscular dystrophy (DMD) is one of the most frequent and severe childhood muscle diseases. Its pathophysiology is multifaceted and still incompletely understood, but we and others have previously shown that oxidative stress plays an important role. In particular, we have demonstrated that inhibition of mitochondrial monoamine oxidases could improve some functional and biohumoral markers of the pathology. In the present study we report the use of dystrophic mdx mice to evaluate the efficacy of a dual monoamine oxidase B (MAO-B)/semicarbazide-sensitive amine oxidase (SSAO) inhibitor, PXS-5131, in reducing inflammation and fibrosis and improving muscle function. We found that a one-month treatment starting at three months of age was able to decrease reactive oxygen species (ROS) production, fibrosis, and inflammatory infiltrate in the tibialis anterior (TA) and diaphragm muscles. Importantly, we also observed a marked improvement in the capacity of the gastrocnemius muscle to maintain its force when challenged with eccentric contractions. Upon performing a bulk RNA-seq analysis, PXS-5131 treatment affected the expression of genes involved in inflammatory processes and tissue remodeling. We also studied the effect of prolonged treatment in older dystrophic mice, and found that a three-month administration of PXS-5131 was able to greatly reduce the progression of fibrosis not only in the diaphragm but also in the heart. Taken together, these results suggest that PXS-5131 is an effective inhibitor of fibrosis and inflammation in dystrophic muscles, a finding that could open a new therapeutic avenue for DMD patients.